1982
DOI: 10.1149/1.2123936
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Inclusions in Indium Phosphide

Abstract: A detailed examination of unusual inclusions in InP substrates has been undertaken. Techniques employed have included optical microscopy, scanning electron microscopy, reflection and transmission x-ray topography, conventional and high voltage electron microscopy, electron diffraction, energy dispersive x-ray analysis, and Auger emission spectroscopy. Inclusions have been detected in many, but not all, undoped, Fe-, Sn-, and Ge-doped InP ingots, at densities from -I0 "~ to I04 cm-'-'. Larger inclusions consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The large bright pits with specific shapes in Fig. 2a are dislocation clusters, a kind of defect in LECgrown InP [17,18]. This was revealed by the following dislocation etch study, that indicated the dislocation clusters originated from the asgrown undoped InP samples which were used for annealing.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The large bright pits with specific shapes in Fig. 2a are dislocation clusters, a kind of defect in LECgrown InP [17,18]. This was revealed by the following dislocation etch study, that indicated the dislocation clusters originated from the asgrown undoped InP samples which were used for annealing.…”
Section: Resultsmentioning
confidence: 83%
“…2b shows that the surface of as-grown undoped InP wafer sample AN-01 has an 'orange peel' aspect and it is easy to discriminate between low-and high-dislocation areas. Such a surface characteristic is caused by the cell distribution of dislocations in InP [17][18][19][20]. Impurities in the sample accumulate around the dislocations by Cottrell force interaction [21,22], resulting in the 'orange peel' like surface revealed by A-B solution.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical etching is the simplest method for revealing dislocations and other defects in crystals. A number of papers have been published recently dealing with chemical, electrochemical, and photochemical etching of InP (7)(8)(9)(10)(11), InGaAs (12,13), and InGaAsP grown on <111> B InP (14,15). However, the <100> orientation is widely utilized for LED's, lasers, and other devices, but no chemical etchant that selectively reveals dislocations in <100> InGaAsP layers has yet been reported.…”
mentioning
confidence: 99%